2020
DOI: 10.1038/s41598-020-71468-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of NUDT15 variants by targeted sequencing can identify compound heterozygosity in pediatric acute lymphoblastic leukemia patients

Abstract: Mercaptopurine intolerance is an adverse effect of mercaptopurine administration in pediatric acute lymphoblastic leukemia. Recently, NUDT15 variants were identified as a major determinant of mercaptopurine intolerance. Two NUDT15 variants, c.36_37insGGAGTC and c.415C > T, are located on exons 1 and 3, respectively. Patients with heterozygous c.36_37insGGAGTC and c.415C > T can be either compound heterozygous with two variants on different alleles or heterozygous w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Pediatric leukemia studies have revealed that patients with this variant can tolerate only 8% of the usual PA dose and account for approximately 22% of PA intolerance cases. [ 14 , 15 ] In vivo and in vitro studies of NUDT15 *3 have revealed that this variant does not affect enzyme activity; instead, it causes instability in NUDT15 protein structure, leading to early protein degradation in cells. Physiologically, diplotype *2/*3 makes enzyme NUDT15 no function at all.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric leukemia studies have revealed that patients with this variant can tolerate only 8% of the usual PA dose and account for approximately 22% of PA intolerance cases. [ 14 , 15 ] In vivo and in vitro studies of NUDT15 *3 have revealed that this variant does not affect enzyme activity; instead, it causes instability in NUDT15 protein structure, leading to early protein degradation in cells. Physiologically, diplotype *2/*3 makes enzyme NUDT15 no function at all.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in sequencing technologies using next-generation sequencing (NGS) approaches allow allelic phasing based on mapping of paired-end sequencing reads, enabling the differentiation between NUDT15 *1/*2 and NUDT15 *3/*6 diplotypes. Yu et al developed a method using NGS to sequence messenger RNA (mRNA)-derived complementary DNA to determine NUDT15 haplotypes [ 21 ], which was able to differentiate between NUDT15 *1/*2 and NUDT15 *3/*6 diplotypes. This method detects NUDT15 variants on expressed transcripts, and serves as an “indirect” method for studying the genomic sequence of NUDT15 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the NUDT15*3 , we failed to identify additional polymorphisms in NUDT15 exon 1 that has been reported to play role in 6-MP intolerance. 28 , 29 It is possible that additional confounding genetic/non-genetic factors could also contribute to increased tolerance, especially in patients homozygous for NUDT15 c.415C>T polymorphism in the Indian population compared to other ethnicities, which needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%